Contact Force and Dynamic Behavior of Automobile Wiper Blade System - Salleh, I; Z. Md Zain, M; R. Abu Bakar, A (International Journal of Engineering and Technology, 2018)
Windscreen wiper vibration problem is now becoming one of the comforts and safety concerns because it can be annoying to the driver and passengers and also affect concentration of the driver while driving. This paper investigate the problems by measuring the wiper blade contact force and vibration level on laboratory wiper experimental rig and wiper system on two different sedan passenger cars operated similarly. In order to measure the vibration and contact force along the wiper blade, MMA7660 accelerometer and a thin film force sensor FSR was used. The contact force is measured at four points; Points 1 (inner tip), 2 (middle blade) and 3 (middle blade) and Point 4 (outer tip), along the wiper blade. Based on the measurement, it was found that the contact force is much higher at Points 1, Point 2 and Point 3 compared to Point 4. For vibration level, higher vibration is occurred at Points 2 and Point 3. It can be conclude that the bigger the contact force value act on windscreen the bigger for the vibration level to be produce. From this founding, further research can be conducted and tackle the problem at certain point along the wiper blade.Â Â